Penerapan Algoritma Random Forest Dalam Klasifikasi Penjurusan Di SMA Negeri Tugumulyo - Marlina, Haiza; Elmayati, E; Zulius, Antoni; Wijaya, Harma Oktafia Lingga (LPPM STIKOM Tunas Bangsa, 2023)
The problem in this study is the difficulty in determining the majors at Tugumulyo State High School, for that a classification model is needed that can determine the right majors in student majors at Tugumulyo State High School. This research uses data collection methods, by observing and recording directly at the research site (observation), asking questions directly to the source (interview), and documentation by reading literature guidelines. The results showed that the majors classification model using the Random Forest algorithm. It can be concluded that the model built using the R programming language gets an accuracy value of 0.9314 and is included in the good classification category.